Crystal orientation dependence of the stress-induced martensitic transformation in zirconia-based shape memory ceramics - Zeng, Xiao Mei (2016)
Small volume samples of zirconia can survive stress-induced martensitic transformation without cracking, which enables in-depth explorations of martensite mechanics using micro-scale specimens. Here we present a systematic investigation of the orientation dependence of tetragonal crystals undergoing a uniaxial stress-driven martensitic transformation to the monoclinic phase, in single crystal zirconia pillars doped with yttria and titania. The Young’s modulus, martensitic transformation stress and transformation strain are highly dependent on the crystallographic orientation, and generally align with expectations based on known tensor properties and transformation crystallography. However, in some orientations, fracture or plastic slip are apparently preferred to martensitic transformation, and thus crystallography favors certain orientations if superelasticity or shape memory properties are specifically desired in zirconia ceramics.